CHINA’S RELATIONS WITH, DEVELOPING COUNTRIES INDONESIA - Flori Mardiani Lubis (Jurnal Politikom Indonesiana, 2017)
With China's dynamic economic growth, the exchanges of high-level visits between China and other developing countries have strengthened political consultation and expanded their economic and trade cooperation.The Indonesian archipelago has been an important trade region since at least the seventh century, when the Srivijaya Kingdom traded with China and India. Local rulers gradually adopted Indian cultural, religious and political models from the early centuries, Hindu, Buddhist and Islam.Relations between two of the world's most populous nations, China and Indonesia have been developing steadily which have also promoted regional peace and prosperity. China and Indonesia established diplomatic relations on April 13 1950, which was suspended on October 30 1967. And it developed gradually since the resumption of diplomatic relations of the two countries.